Prefrontal cortex connectivity during right and left hand dexterity tests in younger and older adults - Manjiri Kulkarni; Peter Rassam; Pedram Mouseli; Monisha Date; Tamires Mori; Marine Van Hollebeke; Jennifer L. Campos; Dmitry Rozenberg; W. Darlene Reid (PLoS ONE, 2026)
Background Age can negatively impact activation and connectivity among prefrontal cortex (PFC) regions during demanding motor functions, such as hand dexterity tasks. The study objective was to compare functional connectivity between PFC regions during right and left-hand 9-hole peg tests (R9HPT and L9HPT) in younger versus older adults. Methods Two groups were tested: 20 Younger (29 ± 4 years; 10F:10M) and 19 Older (67 ± 12 years; 10F:9M) adults. Healthy right-handed adults performed timed R9HPT and L9HPT. Functional near infrared spectroscopy (fNIRS), positioned over eight PFC regions, provided a surrogate measure of neural activity from baseline to test completion as the change in oxygenated hemoglobin (∆O 2 Hb). Time series analysis of ∆O 2 Hb evaluated connectivity between pairs of PFC regions. Results R9HPT and L9HPT test completion times were longer for Older than Younger adults ( p ≤ 0.001) and secondly, longer during L9HPT than R9HPT for both groups (p ≤ 0.001). Greater ∆O 2 Hb was associated with longer test completion times in 5 of 8 PFC regions in Older adults. Patterns of functional connectivity differed between R9HPT and L9HPT within group and between groups (Younger and Older); both groups showed connectivity between the right lower dorsolateral and left upper medial regions during the L9HPT. The left upper medial, right upper medial, left lower medial and left dorsal lateral were mostly involved with other PFC regions. Interhemispheric PFC connectivity was demonstrated for R9HPT and L9HPT for both age groups. Significant intrahemispheric PFC connectivity was shown for R9HPT and L9HPT in the Older group but only in L9HPT for the Younger group. Conclusion Functional connectivity of the PFC evaluated by fNIRS not only differed in Older versus Younger adults but the ∆O 2 Hb, a surrogate of neural activity, showed more pairing between regions during hand dexterity by the non-dominant hand. Age and non-dominant hand required more connectivity but did not lead to improved task efficiency.